2017
DOI: 10.2175/106143017x14839994522902
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Removal Characteristics of Titanium Salts Compared with Aluminum Salt

Abstract: This study evaluates the efficacy of titanium tetrachloride (TiCl4) and titanium sulfate [Ti(SO4)2] on phosphorus (P) removal in synthetic wastewater compared with aluminum sulfate [Al2(SO4)3]. Jar test experiments were performed at various chemical doses and initial pH (pHi) levels to determine the conditions at which P removal was most efficient. The doses with 99% P removal were 0.31 to 0.34 mM for TiCl4, 0.15 mM for Ti(SO4)2, and 0.19 mM for Al2(SO4)3 as Al at 2 mg P/L, 100 mg CaCO3/L, and pHi = 7.0 to 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…TiCl 4 has been found very efficient in removing phosphorous from wastewater. Jeon et al [42] reported that both Ti and Al-based coagulants perform similarly when the initial pH of the feed water is 7, which is in agreement with the current study. At an alkalinity level of 100 mg CaCO 3 /L, they have reported 99% phosphorous removal using a coagulant dose of 0.02 g Ti/L and 0.01 g Al/L, respectively.…”
Section: Coagulation Efficiency Of Ticl 4 Comparing Pacsupporting
confidence: 93%
See 1 more Smart Citation
“…TiCl 4 has been found very efficient in removing phosphorous from wastewater. Jeon et al [42] reported that both Ti and Al-based coagulants perform similarly when the initial pH of the feed water is 7, which is in agreement with the current study. At an alkalinity level of 100 mg CaCO 3 /L, they have reported 99% phosphorous removal using a coagulant dose of 0.02 g Ti/L and 0.01 g Al/L, respectively.…”
Section: Coagulation Efficiency Of Ticl 4 Comparing Pacsupporting
confidence: 93%
“…At an alkalinity level of 100 mg CaCO 3 /L, they have reported 99% phosphorous removal using a coagulant dose of 0.02 g Ti/L and 0.01 g Al/L, respectively. It was reported that an increase in alkalinity of feed water was responsible for the requirement of elevated coagulant doses [42]. Consequently, in the current study, the presence of algae in feed water might have increased the alkalinity, causing an augmented demand of coagulants to remove TP.…”
Section: Coagulation Efficiency Of Ticl 4 Comparing Pacmentioning
confidence: 64%